2004
DOI: 10.1160/th03-12-0755
|View full text |Cite
|
Sign up to set email alerts
|

Immunodominant T-cell epitopes in the factor VIII C2 domain are located within an inhibitory antibody binding site

Abstract: Formation of inhibitor antibodies to factor VIII (FVIII) is a major complication of FVIII replacement therapy for hemophilia A patients, and it occurs through a T-cell dependent process. The C2 domain of FVIII contains epitopes that are recognized by antibody inhibitors. We have examined regions of the C2 domain that form epitopes for T cells in mice congenitally deficient in FVIII. We obtained CD4(+)T cells from mice immunized by intravenous infusion of therapeutic doses of recombinant human FVIII (rFVIII), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Both donors that present this peptide in our study are DRB1*0101 as well. Two other C2 peptides identified in this study were found previously to induce T-cell proliferation (35,37). The fact that most peptides found were donor-specific suggests that these peptides are presented in a HLA-specific context.…”
Section: Quantitative Analysis Of Mhc Class Ii-bound Peptides-tosupporting
confidence: 60%
See 1 more Smart Citation
“…Both donors that present this peptide in our study are DRB1*0101 as well. Two other C2 peptides identified in this study were found previously to induce T-cell proliferation (35,37). The fact that most peptides found were donor-specific suggests that these peptides are presented in a HLA-specific context.…”
Section: Quantitative Analysis Of Mhc Class Ii-bound Peptides-tosupporting
confidence: 60%
“…Proliferation of this clone has been used by another group as a general readout for FVIII endocytosis by dendritic cells (22). Region 2196 -2204 was identified as a region against which CD4ϩ T cells are directed both in a study with hemophilic mice (35) and in a study with a hemophilia A patient (36). This sequence was identified using DRB1*0101 tetramers.…”
Section: Quantitative Analysis Of Mhc Class Ii-bound Peptides-tomentioning
confidence: 99%
“…The immunoprecipitation and inhibitor neutralization assays of the inhibitor plasma from hemophilia A patients clearly indicated that the anti-light chain antibody titer was the highest (12). More recently, Reding et al (13) and Pratt et al (14) have identified several universal epitopes for CD4ϩ T-cells in the 2291-2330 region of the C2 domain using proliferation assays with CD4ϩ cells from normal humans, hemophilia A patients (13), and mice (14). Three-dimensional models proposed based on crystallographic studies and mutational analysis show that the C2 domain also contains 2-4 hydrophobic loops and other charged residues that promote lipid binding ( Fig.…”
mentioning
confidence: 96%
“…[10][11][12] We have shown that recipients of B-cell blasts, transduced with an Ig fusion of a variety of model antigens or autoimmune targets constructs, are tolerant to the protein epitopes of the expressed genes and that this therapy can lead to striking modulation of clinical disease. 8,[13][14][15][16] Importantly, tolerance is more effective and of longer duration in the presence of the IgG backbone 9 (T.C.L., Yan Su, and D.W.S., manuscript in preparation).It is known that most inhibitory antibodies are reactive with conformational epitopes on the exposed surfaces of C2 and A2 domains of fVIII, 1,3,4,17,18 and that immunodominant T-cell epitopes can be found in the C2 region. 17 In this study, we inserted the coding sequences for residues S2173-Y2332 (C2 domain) and S373-R740 (A2 domain) in frame with the IgG heavy chain backbone in a retroviral vector to induce tolerance in hemophilic mice.…”
mentioning
confidence: 99%